Delivering a highly distributed electricity system: Technical, regulatory and policy challenges. (February 2018) - Bell, Keith; Gill, Simon
Abstract: This paper discusses the technical, regulatory and policy challenges inherent in planning and operating power systems with high penetrations of Distributed Energy Resources (DER): generators, flexible demand and energy storage connected within electricity distribution networks. Many liberalised electricity systems worldwide are seeing growth in DER including significant capacities of distributed renewable generation. The paper starts from the premise that optimal distribution networks are those that satisfy the objective of a lowest cost power system whilst meeting customers' expectations of reliability and societal desire for sustainability. It highlights major challenges that policy makers face in respect of market and regulatory arrangements that support energy and flexibility provision from a large number of small, variable and often uncertain resources. These challenges include the need to respect the technical limits of the system and ensure its operability, development of well-designed mechanisms to support innovation, and an appropriate share of risk between market actors. A key contribution of the paper is to discuss the opportunities offered by more active distribution system operation as a substitute for capital investment and its regulatory and policy implications. Finally, the paper presents priorities for policy to facilitate a highly distributed electricity system. Highlights: Impact of increased Distributed Energy Resources into power system on policy needs. Development should focus on low costs within appropriate sustainability and security constraints. Key issues include sharing of risk and information, locationality and timing of pricing. Reviews existing and developing arrangements across regulated and non-regulated sectors. Concludes with 6 key principles for system design and policy implications.